Kinerja Pembangunan Daerah Berdasarkan Indeks Pembangunan Manusia - Didit Purnomo; Diyan Utami; Agung Slamet Sukardi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The Human Development Index (HDI) is one of the parameters usedto measure development success. HDI is measured based on the levelof education, health and expenditure. Central Java Province has alower HDI value compared to other provinces in Java and is lowerthan its national level and only superior to East Java. So that thesample used in this research is 35 regencies/cities in Central JavaProvince during 2015-2018. The type of data used is secondary datasourced from BPS Central Java and other sources related toresearch. The dependent variable in this study was the HDI and theindependent variable consisted of poverty level, population, inflation,GRDP and regency/city minimum wages in Central Java Province.This study aims to see how the influence of the independent variableson the dependent variable using panel data analysis techniquesthrough the best model selection test, namely the chow test and thehausman test. Where chosen the best regression results Fixed EffectModel which shows that the poverty level variable has a negative andsignificant effect on HDI, economic growth variables and district /city minimum wages have a positive and significant effect on HDI,while the population and inflation variables do not have a significanteffect on HDI in Central Java Province.